Escape Philosophy Journeys Beyond the Human Body - Christopher, Roy (punctum books, 2022)
The physical body has often been seen as a prison, as something to be escaped by any means necessary: technology, mechanization, drugs and sensory deprivation, alien abduction, Rapture, or even death and extinction. Taking in horror movies from David Cronenberg and UFO encounters, metal bands such as Godflesh, ketamine experiments, AI, and cybernetics, Escape Philosophy is an exploration of the ways that human beings have sought to make this escape, to transcend the limits of the human body, to find a way out. As the physical world continues to crumble at an ever-accelerating rate, and we are faced with a particularly 21st-century kind of dread and dehumanization in the face of climate collapse and a global pandemic, Escape Philosophy asks what this escape from our bodies might look like, and if it is even possible.